PENGARUH METODE LATIHAN TERHADAP KETEPATAN MENENDANG KE GAWANG PADA PEMAIN FUTSAL PATRIOT PROGRAM STUDI PENJASKESREK FKIP UNPATTI - Liontin Violita Kolly; Johni Melvin Tahapary (JARGARIA SPRINT: Journal Science of Sport and Health, 2020)
The purpose of this study was to determine whether there was an effect of the training method on the accuracy of kicking at the goal of the FKIP Unpatti futsal player Patriot Patriotek. This research is an experimental study, where the author wants to know the ability of futsal player Patriot Penjaskesrek to improve shooting accuracy, with a one group pre-test-post-test-design research design. The method used in this study is an experimental method based on the reference Suarsimin Arikunto. Based on the results of submitting a hypothesis in this study that there is the effect of the training method on the accuracy of kicking at the goal of the Futsal Patriot player of the FKIP Unpatti Penjaskesrek Study Program. This shows that Squat, Heel raise, Cones drill, and Kick to the goal exercises can significantly influence the ability to kick into the goal so that it can be explained that the Exercise Squat, Heel raise, Cones drill, and Kick to the goal is one alternative that can used to improve the ability to kick into the goal on the Futsal Club Patriot FKIP Unpatti Study Program Penjaskesrek.